Mixed esterified polysaccharide and method for producing the same
A novel esterification process using a protic amide solvent and sulfuric acid produces mixed esterified polysaccharides with controlled group ratios, addressing the lack of hydrophilic and hydrophobic properties in existing methods, enabling dispersion in various solvents and resin applications.
Patent Information
- Application Number
- JP2023093884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
AI Technical Summary
Existing methods for modifying polysaccharides do not efficiently produce mixed esterified polysaccharides with both sulfate ester and acyl groups, lacking in hydrophilic and hydrophobic properties necessary for dispersion in various solvents and resins.
A method involving a mixed esterification reaction using a protic amide solvent, monobasic carboxylic acid anhydride, and sulfuric acid is used to simultaneously sulfate esterify and acylate polysaccharides without pre-treatment, allowing for the production of mixed esterified polysaccharides with controlled molar ratios of sulfate ester and acyl groups.
The method enables the synthesis of mixed esterified polysaccharides that are dispersible in both aqueous and organic solvents, maintaining the crystal structure and enabling applications as surfactants, dispersants, and reinforcing materials.
Smart Images

Figure 2024175841000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to mixed esterified polysaccharides and mixed esterified polysaccharide nanofibers, and to a method for producing the same. [Background technology]
[0002] The applicant has filed numerous patent applications for inventions relating to modified cellulose nanofibers produced using a defibrating solution containing a monobasic carboxylic acid anhydride (acetic anhydride, propionic anhydride, butyric anhydride, etc.) as a reactant or catalyst. For example, examples of inventions relating to cellulose nanofibers modified with hydrophobic monobasic carboxylic acids that provide good dispersibility in organic media include an invention in which cellulose nanofibers are obtained by esterification with monobasic carboxylic acids using a defibrating solution containing a base catalyst or organic acid catalyst and a monobasic carboxylic acid anhydride as a reactant in an aprotic solvent with a donor number of 26 or more (Patent Document 1), and an invention in which cellulose nanofibers are obtained by esterification with monobasic carboxylic acids using a defibrating solution containing formic acid or a high-concentration formic acid aqueous solution and a monobasic carboxylic acid anhydride as a reactant (Patent Document 2). Another invention relating to sulfate ester modified cellulose nanofibers that have hydrophilicity and are easily dispersible in water is an invention in which sulfate ester modified cellulose nanofibers are obtained by using a defibrating solution containing dimethyl sulfoxide, a monobasic carboxylic acid anhydride as a catalyst, and sulfuric acid as a reactant (Patent Document 3). Another invention relates to hydrophilic dicarboxylic acid monoesterified cellulose nanofibers that disperse easily in the same water as sulfate esterified modified cellulose nanofibers, and is an invention in which dicarboxylic acid monoesterified cellulose nanofibers are obtained using a solution containing a protic amide solvent and a dicarboxylic acid anhydride (Patent Document 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 073700 [Patent Document 2] International Publication No. 2017 / 208600 [Patent Document 3] International Publication No. 2018 / 131721 [Patent Document 4] Patent application No. 2020-134492 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides mixed-esterified polysaccharides in which hydroxyl groups of a polysaccharide are modified with sulfate ester groups and acyl groups by simultaneously sulfate-esterifying and acylating a polysaccharide, and polysaccharide nanofibers, and a method for producing the same. [Means for solving the problem]
[0005] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have discovered a method for producing mixed esterified polysaccharides without the need for a pretreatment of polysaccharides, and have succeeded in obtaining mixed esterified polysaccharides.
[0006] That is, the present invention is characterized by having the following configuration and solves the above-mentioned problems. [1] A mixed esterified polysaccharide, characterized in that the hydroxyl groups of the polysaccharide are modified with a sulfate ester group and an acyl group. [2] The mixed esterified polysaccharide according to claim 1 in [1], characterized in that the modification rate of the hydroxyl groups is 0.3 to 19 mmol / g and the molar ratio of sulfate ester groups / acyl groups is 10 / 90 to 99 / 1. [3] The mixed esterified polysaccharide according to [1], characterized in that the modification rate of the hydroxyl groups is 0.3 to 12.0 mmol / g, the molar ratio of sulfate ester groups / acyl groups is 10 / 90 to 99 / 1, and the mixed esterified polysaccharide is a nanofiber having an average fiber diameter of 1 nm to 500 nm. [4] The mixed esterified polysaccharide according to any one of [1] to [3] above is a mixed esterified polysaccharide characterized in that it can be dispersed or dissolved in water or one or more organic solvents selected from the group consisting of DMSO, DMAc, DMF, amide solvents, alcohols, and ether solvents. [5] A method for producing a mixed esterified polysaccharide, comprising: permeating and swelling a polysaccharide with a mixed esterification reaction solution containing a protic amide solvent, a monobasic carboxylic acid anhydride, and sulfuric acid, as shown in the following formula (1), and subjecting the polysaccharide to an acylation reaction together with sulfate esterification: R1-C(=O)-NH(R2) (1) (In the formula, R1 and R2 represent a proton or an alkyl group having 1 to 3 carbon atoms. R1 and R2 may be the same or different.) [6] The method for producing a mixed esterified polysaccharide according to [5], wherein the protic amide solvent is at least one of formamide, N-methylformamide, acetamide and N-methylacetamide. [7] The method for producing a mixed esterified polysaccharide according to [5] or [6], characterized in that the concentration of the monobasic carboxylic acid anhydride in the mixed esterification reaction liquid is 0.1 to 50% by weight, and the concentration of sulfuric acid is 0.1 to 50% by weight. [8] The method for producing a mixed esterified polysaccharide according to claim 5 or 6, characterized in that in the mixed esterification reaction liquid, the concentration of the monobasic carboxylic acid anhydride is 0.1 to 25% by weight, the concentration of the sulfuric acid is 0.1 to 20% by weight, and the mixed esterified polysaccharide is a nanofiber having an average fiber diameter of 1 nm to 500 nm. Effect of the Invention
[0007] According to the production method of the present invention, a mixed sulfated and acylated esterified polysaccharide can be synthesized in a single reaction. In the production method of the present invention, the reaction takes place even at room temperature, but heating promotes the sulfate ester or acylation reaction, making it possible to shorten the reaction time.
[0008] In the production method of the present invention, the reaction solution (defibration solution) contains a protic amide solvent, sulfuric acid, and a monobasic carboxylic anhydride, and has few side reactions, excellent permeability and swelling properties for polysaccharides such as cellulose, chitin, and chitosan, and can produce mixed esterified polysaccharides by simultaneously modifying polysaccharides with sulfate esterification and acylation at a temperature range close to room temperature. Furthermore, by controlling the concentrations of the monobasic carboxylic anhydride and sulfuric acid within a certain range, the crystal structure of the polysaccharide can be maintained and the mixed esterified polysaccharide nanofibers can be produced by simultaneously modifying the polysaccharides with sulfate esterification and acylation.
[0009] The reaction solution of the present invention penetrates between polysaccharide fibrils to modify the hydroxyl groups on the surface of the polysaccharide fibrils with sulfate esters and carboxylate esters, and then electrostatic repulsion and shear force are applied to produce mixed esterified polysaccharide nanofibers.
[0010] The mixed esterified polysaccharide nanofiber of the present invention has high transparency due to the small average fiber diameter of CNF and narrow fiber diameter distribution. In addition, since it has hydrophilic sulfate groups and hydrophobic acyl groups, it can be dispersed in various organic solvents and resins, and when it is composited with resin as a reinforcing material, it can both reinforce and ensure the transparency of the resin. [Brief description of the drawings]
[0011] [Figure 1] IR spectrum of Example 1 [Diagram 2] IR spectrum of Example 2 [Diagram 3] IR spectrum of Example 3 [Figure 4] Photographs of aqueous dispersions of mixed esterified polysaccharide nanofibers (0.3%) prepared in Examples 4 to 12 [Diagram 5] SEM photo of Example 4 [Figure 6] SEM photo of Example 7 [Figure 7] Pyrolysis GC-MS Analysis Results of Example 7 [Figure 8] SEM photo (left) and TEM photo (right) of Example 9 [Figure 9] SEM photo (left) and TEM photo (right) of Example 11 [Figure 10] SEM photo (left) and TEM photo (right) of Example 12 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The mixed esterified polysaccharide of the present invention is a mixed esterified polysaccharide in which the hydroxyl groups of the polysaccharide are modified with sulfate ester groups and acyl groups. The acyl group to modify the hydroxyl group is not particularly limited, but examples thereof include aliphatic acyl groups such as acetyl, propionyl, butyryl, isobutyryl and lauroyl groups, and aromatic acyl groups such as benzoyl and cinnamoyl groups. Mixed esterified polysaccharides have both hydrophobic and hydrophilic properties due to the presence of sulfate ester groups and acyl groups, and can be used as surfactants, dispersants, moisturizing agents, and thickeners.
[0013] In the mixed esterified polysaccharide of the present invention, the modification rate of the hydroxyl groups is preferably 0.3 to 19 mmol / g, and the molar ratio of sulfate ester groups / acyl groups is preferably 10 / 90 to 99 / 1.
[0014] The modification ratio of the mixed esterified polysaccharide of the present invention refers to the total number of moles of hydroxyl groups substituted with sulfate ester groups and acyl groups per g of polysaccharide. Since there are a maximum of three hydroxyl groups per anhydroglucan unit of the polysaccharide, the theoretical maximum modification ratio is about 19 mmol / g when all hydroxyl groups are substituted. If the modification ratio is too low, the effects of surfactants, dispersants, moisturizing agents, thickeners, etc. cannot be obtained, so the modification ratio of the present invention is preferably 0.3 to 19 mmol / g. More preferably, it is 0.5 to 18 mmol / g, even more preferably 0.8 to 17 mmol / g, and most preferably 1.0 to 16 mmol / g.
[0015] The molar ratio of sulfate ester group / acyl group is preferably 10 / 90 to 99 / 1. The optimal molar ratio varies depending on the type of acyl group. For example, if the acyl group is an aliphatic acyl group having 6 or less carbon atoms, the ratio of sulfate ester group / acyl group is preferably on the lower side. On the other hand, if the acyl group is an acyl group having 12 or more carbon atoms such as a lauryl group, the ratio is preferably on the higher side. If the ratio is lower than 10 / 90, the hydrophilicity of the mixed esterified polysaccharide obtained is low, and the surfactant effect, physiological activity, or biological activity derived from the sulfate ester group may be reduced, which is not preferable. On the other hand, if the ratio is higher than 99 / 1, the characteristics derived from the acyl group, such as dispersibility in an organic medium, are reduced, which is not preferable. Therefore, a more preferable molar ratio of sulfate ester group / acyl group is 15 / 85 to 98 / 2. More preferably, it is 20 / 80 to 95 / 5, and even more preferably, it is 25 / 75 to 90 / 10.
[0016] The dispersibility or solubility of the mixed esterified polysaccharide in water or an organic solvent depends on the sulfate modification rate and the acylation modification rate. The higher the sulfate modification rate, the easier the mixed esterified polysaccharide is to disperse or dissolve in water. On the other hand, the higher the acylation modification rate, the easier the mixed esterified polysaccharide is to disperse or dissolve in an organic solvent. The type of organic solvent in which the mixed esterified polysaccharide is dispersed depends on the type of acyl group, but is not particularly limited. Examples of the organic solvent include alcohols such as ethanol and isopropanol, sulfoxides such as dimethyl sulfoxide, and amides such as dimethylacetamide.
[0017] The form of the mixed esterified polysaccharide is not particularly limited. For example, it can be processed into a solution soluble in water or an organic solvent, a powder, a fiber, a pulp, a film, or the like, depending on the application and the average degree of substitution.
[0018] The mixed esterified polysaccharide of the present invention is a nanofiber having a modification rate of the hydroxyl groups of 0.3 to 12.0 mmol / g, a molar ratio of sulfate ester groups / acyl groups of 10 / 90 to 99 / 1, and an average fiber diameter of 1 nm to 500 nm.
[0019] If all hydroxyl groups are substituted, hydrogen bonds between polysaccharide molecular chains disappear, and the natural type I crystal structure and fibril shape are lost. In order to maintain the crystal structure and nanofiber shape, the modification rate is set within the range of 0.3 to 12.0 mmol / g, and the mixed esterified polysaccharide obtained has the original natural crystal structure, so that it can be defibrated into nanofibers by disentangling the mixed esterified polysaccharide with electrostatic repulsion or shear force. If the modification rate is lower than 0.3 mmol / g, the electrostatic repulsion force becomes weak or hydrogen bonds between the nanofibers remain, making it impossible to disentangle the nanofibers to nano sizes, and the fiber diameter of the obtained nanofibers may exceed 500 nm, which is not preferable. On the other hand, if the modification rate exceeds 12.0 mmol / g, the mixed esterified polysaccharide loses almost all of its original natural crystal structure, and mixed esterified polysaccharide nanofibers cannot be obtained.
[0020] Therefore, in order to obtain mixed esterified polysaccharide nanofibers, the modification rate is preferably controlled within the range of 0.3 to 12.0 mmol / g, more preferably 0.5 to 11.0 mmol / g, and most preferably 0.9 to 10.0 mmol / g.
[0021] Also, the molar ratio of sulfate ester group / acyl group is preferably 10 / 90 to 99 / 1. The optimal molar ratio varies depending on the type of acyl group. For example, if the acyl group is an aliphatic acyl group having 6 or less carbon atoms, the ratio of sulfate ester group / acyl group is preferably on the lower side. On the other hand, if the acyl group is an acyl group having 12 or more carbon atoms such as a lauryl group, the ratio is preferably on the higher side. If the ratio is lower than 10 / 90, the hydrophilicity of the mixed esterified polysaccharide nanofiber obtained is low, and the surfactant effect, physiological activity, or biological activity derived from the sulfate ester group may be reduced, which is not preferable. On the other hand, if the ratio is higher than 99 / 1, the characteristics derived from the acyl group, such as dispersibility in an organic medium, are reduced, which is not preferable. Therefore, a more preferable molar ratio of sulfate ester group / acyl group is 15 / 85 to 98 / 2. More preferably, it is 20 / 80 to 95 / 5, and even more preferably, it is 25 / 75 to 90 / 10.
[0022] The fiber diameter and its distribution range of polysaccharide nanofibers are governed by the sulfate esterification modification rate of hydroxyl groups. As the sulfate esterification modification rate increases, the average fiber diameter of polysaccharide nanofibers decreases and the nanofiber distribution becomes narrower. When the sulfate esterification modification rate exceeds a certain value, the fiber diameter of polysaccharide nanofibers becomes almost monodisperse, and the fiber diameter is 10 nm or less. In addition, the higher the sulfate esterification modification rate, the higher the effects of surfactants, dispersants, moisturizing agents, thickeners, etc. become. However, if the modification rate increases, there is a risk of losing crystallinity and fiber shape. Therefore, the sulfate esterification modification rate is preferably 0.01 to 10.8 mmol / g. More preferably, it is 0.05 to 9.5 mmol / g, and most preferably 0.1 to 9.0 mmol / g.
[0023] The average fiber diameter of the mixed esterified polysaccharide nanofiber is preferably 1 nm to 500 nm. If it is smaller than this range, the degree of crystallinity of the polysaccharide may decrease or the crystal structure may be lost, which is not preferable. On the other hand, if it is larger than 500 nm, the surface area of the nanofiber may become small, and the thickening effect, reinforcing effect, dispersing effect, and physiological and biological effects may not be obtained, which is not preferable. Particularly preferably, it is 2 nm to 400 nm, and more preferably, 3 nm to 300 nm.
[0024] The fiber diameter distribution affects the quality and properties of nanofibers. The narrower the distribution, the higher the uniformity of the nanofibers, and the better the mechanical properties, transparency, water absorption and moisture absorption, surface activity, etc. The fiber diameter distribution becomes narrower as the sulfuric acid esterification modification rate increases.
[0025] There is no particular limitation on the form of the mixed esterified polysaccharide nanofibers, and they can be processed into a dispersion form in water or an organic solvent, a powder, a film, or the like, depending on the application.
[0026] The solubility or dispersibility of mixed esterified polysaccharides in solvents depends on the molar ratio of the total modification rate, the sulfate modification rate, and the acylation modification rate. The higher the total modification rate, the higher the solubility or dispersibility in solvents. The solvent in which it dissolves depends on the molar ratio of sulfate ester groups to acyl groups. The more sulfate esters there are, the more it dissolves or disperses in polar solvents such as water and alcohols. On the other hand, the higher the molar ratio of acyl groups, the more it dissolves or disperses in solvents with low polarity.
[0027] The dispersibility of mixed esterified polysaccharide nanofibers in water or organic solvents depends on the sulfate esterification modification rate and the acylation modification rate. The higher the sulfate esterification modification rate, the easier the mixed esterified polysaccharides are to disperse in water. On the other hand, the higher the acylation modification rate, the easier the mixed esterified polysaccharides are to disperse in organic solvents. The type of organic solvent depends on the type of acyl group, but is not particularly limited. Examples include alcohols such as ethanol and isopropyl alcohol, sulfoxides such as dimethyl sulfoxide, and amides such as dimethylacetamide.
[0028] The mixed esterified polysaccharide nanofibers of the present invention, even once dried, can be dispersed in water or one or more organic solvents, such as amide solvents, such as DMSO, DMAc and DMF, alcohols, such as methanol, ethanol or isopropanol, and ether solvents, such as ethers of ethylene glycol or ethers of propylene glycol. Specifically, even if the dispersion solvent is removed from the dispersion liquid of the nanofibers of the mixed esterified polysaccharides of the present invention and the dispersion liquid is dried, it can be dispersed again by adding it to a dispersion medium. The method for removing the dispersion solvent is not particularly limited, but examples thereof include air drying, atmospheric distillation, reduced pressure distillation, freeze drying, and dry spray. The dry state is not particularly limited, but the nanofibers can be redispersed in any of the film, powder, chip, and flake forms.
[0029] Depending on the dryness and size of the particles, a dispersion method may be applied during redispersion, such as a magnetic stirrer method, mechanical stirring method, ultrasonic treatment method, or homogenizer method.
[0030] The visible light transmittance of the mixed esterified polysaccharide nanofiber dispersion is related to the fiber diameter of the nanofiber and the molar ratio of sulfate ester groups / acyl groups. The smaller the fiber diameter or the more sulfate ester groups, the higher the visible light transmittance. There are no particular limitations on the visible light transmittance, but it is preferably 40 to 96%. It is particularly preferably 50 to 95%, and most preferably 55 to 93%.
[0031] The mixed esterified polysaccharide or polysaccharide nanofiber of the present invention has a sulfate ester group and an acyl group, and therefore has excellent affinity with aqueous and non-aqueous media, and is expected to be used as a surfactant or thickener. In addition, by controlling the molar ratio of the sulfate ester group and the acyl group, it is expected to be used as a surfactant not only for O / W emulsions in which oil droplets are dispersed in water (continuous phase) but also for W / O emulsions in which water droplets are dispersed in oil (continuous phase).
[0032] Furthermore, while the chemical properties are the same whether or not the crystalline fibril shape of natural cellulose is maintained, maintaining the crystalline fibril shape not only provides a thickening effect and a surfactant effect, but also allows for application as a reinforcing material.
[0033] The mixed esterified polysaccharide of the present invention can be produced by impregnating and swelling a polysaccharide with a mixed esterification reaction solution containing a protic amide solvent, a monobasic carboxylic acid anhydride, and sulfuric acid, as shown in the following formula (1), and by subjecting the surfaces of the polysaccharide fibrils to sulfuric acid esterification and acylation reactions. R1-C(=O)-NH(R2) (1) (In the formula, R1 and R2 represent a proton or an alkyl group having 1 to 3 carbon atoms. R1 and R2 may be the same or different.)
[0034] The polysaccharides used as raw materials in the present invention include oligosaccharides and are not particularly limited. Major polysaccharides include cellulose, chitin or chitosan, starch, sucrose, hyaluronic acid, glycogen, agarose, pectin, etc.
[0035] The cellulose used as the raw material in the present invention may be in the form of cellulose alone or in a mixed form containing non-cellulose components such as lignin and hemicellulose. Examples of cellulose in a pure form (or cellulose with a small content of non-cellulose components) include pulp (e.g., wood pulp, bamboo pulp, straw pulp, bagasse pulp, linter pulp, flax pulp, hemp pulp, paper mulberry pulp, mitsumata pulp, etc.), sea squirt cellulose, bacterial cellulose, cellulose powder, crystalline cellulose, etc. Examples of mixed forms of cellulose (cellulose compositions) include wood (e.g., conifers (pine, fir, spruce, hemlock, cedar, etc.), broad-leaved trees (beech, birch, poplar, maple, etc.)), herbaceous plants (hemp (hemp, flax, Manila hemp, ramie, etc.), straw, bagasse, Mitsumata, etc.), seed hair fibers (cotton linters, bombax cotton, kapok, etc.), bamboo, sugar cane, paper, etc.
[0036] These celluloses can be used alone or in combination of two or more. In the mixed form of cellulose, the ratio of non-cellulose components such as lignin and protein may be 90% by weight or less, for example, 1 to 90% by weight, preferably 3 to 80% by weight, and more preferably about 5 to 70% by weight. If the ratio of other components is too high, it may be difficult to produce mixed esterified modified CNF.
[0037] The cellulose preferably contains crystalline cellulose (particularly type I crystalline cellulose), and may be a combination of crystalline cellulose and non-crystalline cellulose (such as amorphous cellulose). The proportion of crystalline cellulose (particularly type I crystalline cellulose) may be 10% by weight or more based on the total cellulose, for example, 30 to 99% by weight, preferably 50 to 98.5% by weight, and more preferably about 60 to 98% by weight. If the proportion of crystalline cellulose is too low, the heat resistance and strength of the mixed esterification modified CNF may be reduced. On the other hand, either the crystalline or non-crystalline form can be used to synthesize mixed esterification polysaccharides other than the mixed esterification modified CNF.
[0038] Among these, wood pulp (e.g., softwood pulp, hardwood pulp, etc.), seed hair fiber pulp (e.g., cotton linter pulp), cellulose powder, etc. are commonly used because they are easy to modify and defibrate. The pulp may be mechanical pulp obtained by mechanically treating pulp material, but chemical pulp obtained by chemically treating pulp material is preferred because it has a low content of non-cellulose components.
[0039] The raw material chitin or chitosan may be in the form of chitin alone, or may be in the form of a mixture containing non-chitin components such as crustaceans such as crabs, shrimps, or insects, squids, shellfish, etc. It is also preferable to demineralize or deproteinize crustaceans, squids, shellfish, etc. before use.
[0040] The water content of the raw material polysaccharide (weight ratio of water to dry polysaccharide) is not particularly limited, but may be 1% by weight or more, for example, about 1 to 100% by weight, preferably 2 to 80% by weight, and more preferably about 3 to 60% by weight (particularly 5 to 50% by weight). In the present invention, from the viewpoint of the permeability or swelling efficiency of the reaction solution, it is preferable that the polysaccharide contains water in such a range, and for example, in the case of commercially available cellulose pulp, chitin, or chitosan, they may be used as they are without drying. If the water content is too low, the permeability of the reaction solution may decrease.
[0041] The mixed esterification reaction liquid is preferably a monobasic carboxylic acid anhydride, such as an aliphatic carboxylic acid anhydride, e.g., acetic anhydride, propionic anhydride, butyric anhydride, isobutyric anhydride, pentanoic anhydride, hexanoic anhydride, or lauric anhydride, or an aromatic carboxylic acid anhydride, e.g., benzoic anhydride.
[0042] Further, preferred carboxylic acid anhydrides are acetic anhydride, butyric anhydride, isobutyric anhydride, lauric anhydride and benzoic anhydride, which are preferred because they are readily available commercially.
[0043] The protic amide solvent represented by the formula (1) is preferably a protic amide solvent having a dielectric constant of 45 or more at room temperature and an acceptor number of 20 or more. Examples of the protic amide solvent include formamide (FA), N-methylformamide (MFA), N-ethylformamide, acetamide, N-methylacetamide, and N-ethylacetamide. Preferred are formamide, methylformamide, acetamide, and N-methylacetamide, and most preferred are formamide and methylformamide.
[0044] The solvent used in the production of mixed esterified polysaccharide nanofibers must be able to dissolve the reactant, and the four most important properties are the rate of penetration into the polysaccharide, the degree of swelling of the polysaccharide, and the ability to promote the modification reaction. These properties are thought to govern the fiber diameter and uniformity of the modified polysaccharide nanofibers.
[0045] Protic amide solvents, particularly formamide, N-methylformamide, acetamide and N-methylacetamide, have both of these effects and are suitable for heating reactions due to their high solvent boiling points. In addition, protic amide solvents are preferred because they are believed to have a high effect of stabilizing anions through solvation. Furthermore, protic amide solvents are different from general protic polar solvents in that they have a low ability to donate or release protons from the solvent itself, making competitive reactions less likely to occur.
[0046] As long as the reaction solution does not reduce the permeability of the polysaccharide or cause side reactions, an aprotic solvent such as DMAc, DMF, NMP, DMSO, ketones such as acetone, or ethers such as THF may be added.
[0047] The concentration of the monobasic carboxylic acid anhydride contained in the protic amide solvent may be appropriately adjusted depending on the type or reactivity of the anhydride, and the reaction conditions (temperature, time, pulp concentration, presence or absence of catalyst). For example, it is 0.1 to 50% by weight, more preferably 0.5 to 40% by weight, even more preferably 1 to 35% by weight, and most preferably 1.5 to 30% by weight. If the concentration is lower than this range, it is not preferable because the reaction rate may decrease or the modification rate may decrease. Conversely, if the concentration is higher than this range, it is not preferable because the carboxylic acid anhydride may not be completely dissolved or the permeability of the reaction solution into the inside of the polysaccharide may decrease.
[0048] When synthesizing a mixed esterified polysaccharide, the concentration of sulfuric acid in the mixed esterification reaction solution is preferably 0.1 to 50% by weight. If it is lower than 0.1% by weight, it is not preferable because there is a risk that sulfate esterification and acylation modification may not be possible. If it exceeds 50% by weight, it is not preferable because there is a risk that the polysaccharide may be hydrolyzed by acid or decomposed by an oxidation reaction. Therefore, the concentration is more preferably 0.2 to 40% by weight, even more preferably 0.3 to 35% by weight, and most preferably 0.5 to 30%.
[0049] On the other hand, when synthesizing mixed esterified polysaccharide nanofibers, the sulfuric acid concentration is preferably 0.1 to 20% by weight. If it is lower than 0.1% by weight, not only the sulfuric acid esterification modification but also the acylation modification may not be possible, which is undesirable. It is more preferably 0.15% by weight, even more preferably 0.25% by weight, and most preferably 0.35% by weight or more. On the other hand, if it exceeds 20% by weight, hydrolysis of the polysaccharide and deterioration of crystallinity are likely to occur, which is undesirable. It is more preferably 16% by weight, even more preferably 12% by weight, and most preferably 10% by weight or less.
[0050] The sulfuric acid used in the reaction is not particularly limited, and may be any commercially available sulfuric acid. If the water content of the sulfuric acid is too high, the reaction rate and the modification rate may decrease, which is not preferable, but the water content is preferably 20% by weight or less, more preferably 15% by weight, and most preferably 10% by weight or less.
[0051] By using the mixed esterification reaction liquid, it is possible to produce a mixed esterified polysaccharide under mild reaction conditions.
[0052] When synthesizing a mixed esterified polysaccharide, the weight ratio of the polysaccharide and the reaction solution is not particularly limited, and may be appropriately controlled depending on the type, shape, and density of the polysaccharide. However, if the ratio is too low, the production efficiency is low. If the ratio is too high, the uniformity of the sulfate ester modification and the acylation modification decreases, and there is a risk that the quality of the resulting mixed esterified polysaccharide cannot be guaranteed. Therefore, the weight ratio of the polysaccharide can be selected from the range of about polysaccharide / reaction solution = 0.5 / 99.5 to 50 / 50, for example, 1 / 99 to 45 / 55, preferably 1.5 / 99.5 to 40 / 60, and more preferably 2 / 98 to 35 / 65.
[0053] On the other hand, when synthesizing mixed esterified polysaccharide nanofibers, the polysaccharide / reaction solution ratio can be selected from the range of about 0.5 / 99.5 to 35 / 65, for example, about 1.2 / 98.8 to 30 / 70, preferably about 1.5 / 98.5 to 25 / 75, and more preferably about 2 / 98 to 20 / 80. If the ratio of polysaccharides is too low, the production efficiency of mixed esterified polysaccharide nanofibers will be low, and if it is too high, the reaction time will be long, so in either case, there is a risk of productivity decreasing. Furthermore, if the ratio of polysaccharides is too high, there is a risk of the uniformity of the size and modification rate of the obtained mixed esterified polysaccharide nanofibers decreasing.
[0054] The method of modifying polysaccharides by sulfate esterification and acylation can be carried out by mixing a mixed esterification reaction liquid with the raw polysaccharide, allowing the mixed esterification reaction liquid to penetrate between the polysaccharide fibrils, and subjecting the hydroxyl groups on the surface of the polysaccharide fibrils to a mixed esterification reaction, thereby defibrating them by electrostatic repulsion.
[0055] The mixed esterification reaction liquid is prepared by mixing a reaction solution containing sulfuric acid, a monobasic carboxylic acid anhydride, and a protic amide solvent represented by the following formula (1). A typical method for preparing a mixed esterification reaction liquid is to mix and stir each component to uniformly dissolve the other components in the solvent.
[0056] The mixed esterification reaction solution and the raw polysaccharide may be mixed by adding the raw polysaccharide to the mixed esterification reaction solution in a reaction vessel, or by adding the mixed esterification reaction solution to the raw polysaccharide in the reaction vessel. On a laboratory scale, a sample bottle or flask can be used as the reaction vessel. For scale-up, a reaction apparatus normally used in organic synthesis is preferable. When the polysaccharide concentration is high, a kneader such as a twin-screw extruder can also be used.
[0057] The mixed esterification reaction is carried out by stirring the mixture of the polysaccharide and the mixed esterification reaction liquid at a predetermined temperature for a predetermined time.
[0058] Stirring may be performed by appropriately selecting from various commonly used stirring methods according to the form of polysaccharide and the weight ratio of polysaccharide to the reaction liquid. In the case of powdered polysaccharides or when the concentration of polysaccharides is low, a stirrer or synthesis device generally used in organic synthesis is applied. On the other hand, when the polysaccharide is fibrous or the polysaccharide concentration is high, a twin-screw kneader or kneader is applied. Basically, the mixed esterified polysaccharide finally obtained differs depending on the shear force of stirring in the reaction stage. If the shear force is too high, the mixed esterified polysaccharide obtained will become fine and difficult to wash. The stirring method used for synthesizing mixed esterified polysaccharides and polysaccharide nanofibers may be the same. There is no particular need to use them separately.
[0059] The shape of the mixed esterified polysaccharides varies depending on the stirring method and the shear force. For example, when mild stirring such as a magnetic stirrer or mechanical stirring is used, the fiber diameter of the obtained product is on the order of microns to several tens of microns. Because of the large shape, separation and washing are highly convenient, and the product can be easily separated and washed by normal methods such as filtration, pressure filtration, and squeezing. On the other hand, when a powerful stirring method such as a paint shaker is used, most polysaccharides can be made nanoscale after modification, but the resulting mixed esterified polysaccharides are difficult to separate and wash by normal separation methods such as filtration, and complicated separation and washing methods are required. Therefore, the reaction method should be appropriately selected depending on the application and purpose.
[0060] The reaction temperature is preferably 15°C to 200°C. If it is lower than 15°C, the reaction rate is low and the required reaction time is long, which is not preferable. If it is higher than 200°C, the polysaccharide may decompose, which is not preferable. The reaction temperature is more preferably 20 to 150°C, and most preferably 23 to 120°C.
[0061] The reaction can be carried out in an air atmosphere, but in the case of a reaction at high temperature, it is preferable to carry out the reaction under an inert gas in order to avoid oxidation of the reactant or polysaccharide. By carrying out the reaction under an inert gas, side reactions can be suppressed, which is preferable. Either nitrogen or argon gas can be used as the inert gas.
[0062] The reaction time may be appropriately adjusted depending on the temperature and the type and concentration of the esterification reaction liquid. For example, at room temperature, the reaction time is preferably 6 to 24 hours. The reaction time can be shortened by heating or increasing the temperature. For example, when heated to 40 to 80° C., the reaction time can be shortened to 30 minutes to 6 hours.
[0063] A short reaction time is not preferred because it may result in a low modification rate or uneven distribution of the modified functional groups, making it difficult to guarantee the quality of the resulting mixed esterified polysaccharide, whereas a too long reaction time is not preferred because it not only reduces the production efficiency but also may cause decomposition of the polysaccharide.
[0064] Next, the mixed esterified polysaccharide obtained by the reaction is separated and washed from the reaction solution containing the mixed esterified polysaccharide, thereby removing the protic amide solvent, sulfuric acid, carboxylic acid anhydride, etc. in the reaction solution, and the mixed esterified modified polysaccharide is recovered. The washing solvent is not particularly limited, but may be any solvent capable of dissolving each component of the reaction solution, and is preferably, for example, water, alcohol, or a mixture of water and alcohol. The washing method is not particularly limited, but possible methods include squeezing, pressure filtration, reduced pressure filtration, centrifugation, and precipitation.
[0065] Depending on the reaction conditions, it may be preferable to neutralize the reaction mixture with a neutralizing alkali during washing. The neutralizing alkali is not particularly limited, but examples thereof include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, and lithium carbonate, and amine compounds.
[0066] The state of the recovered mixed ester modified polysaccharide is not particularly limited. For example, after washing, it may be in a wet state still containing a protic solvent such as water, or in a dry state. Even if the recovered modified polysaccharide is dried, it will disperse again when water is added.
[0067] The shape of the recovered mixed ester modified polysaccharide varies depending on the reaction conditions and stirring conditions during the modification reaction, but is usually fibrous with a fiber diameter of several μm to tens of μm, fine fiber with a fiber diameter of several hundred nm to 1000 nm, or polysaccharide nanofiber with a fiber diameter of 3 nm to 100 nm. The faster the stirring speed, the lower the content of fibers of the order of microns or more in the obtained anionic cellulose because defibration occurs during the reaction. However, if the stirring is too strong, the polysaccharide is decomposed to the nanoscale during the reaction, which reduces the water-releasing property during washing, increases the amount of washing solvent required for washing, or increases the washing time, which may lead to a decrease in production efficiency.
[0068] The method for producing mixed esterified polysaccharide nanofibers of the present invention, which are nanofibers having an average fiber diameter of 1 nm to 500 nm, uses a mixed esterification reaction solution having a monobasic carboxylic acid anhydride concentration of 0.1 to 25 wt % and a sulfuric acid concentration of 0.1 to 20 wt %, thereby producing nanofibers having a modification rate of hydroxyl groups in the polysaccharide of 0.5 to 9.0 mmol / g, a molar ratio of sulfate ester groups / acyl groups of 10 / 90 to 99 / 1, and an average fiber diameter of 1 nm to 500 nm.
[0069] In the production of mixed esterified polysaccharide nanofibers, the preferred concentration of monobasic carboxylic acid anhydride is 0.1 to 25% by weight, and more preferably 0.2 to 20% by weight. If the concentration is lower than 0.1% by weight, not only acylation but also sulfate esterification cannot be performed. On the other hand, if the concentration exceeds 25% by weight, the mixed esterification reaction solution is unlikely to penetrate into the polysaccharide, which may reduce the efficiency and uniformity of the modification reaction or may make sulfate esterification impossible, which is not preferred. Therefore, the most preferred concentration is 0.5 to 15% by weight.
[0070] In the production of mixed esterified polysaccharide nanofibers, the preferred sulfuric acid concentration is 0.1 to 20% by weight, more preferably 0.2 to 15% by weight, and even more preferably 0.3 to 10% by weight. If the concentration is lower than 0.1% by weight, not only the sulfate esterification but also the acylation cannot be performed. On the other hand, if the concentration exceeds 20% by weight, the polysaccharide may decompose, which is not preferred. Therefore, the most preferred concentration is 0.5 to 10% by weight.
[0071] The mixed esterified polysaccharide nanofibers are produced in the same manner as in the production of the mixed esterified polysaccharides described above, by penetrating the mixed esterification reaction solution into the spaces between the fibrils of the polysaccharide to swell the polysaccharide, and subjecting the surfaces of the polysaccharide fibrils to sulfate esterification and acylation reaction. However, the mixed esterified polysaccharides are produced by defibrating them using electrostatic repulsion or shear force simultaneously with or after the mixed esterification.
[0072] When the mixed esterified polysaccharide is defibrated simultaneously with the mixed esterification, the degree of defibration can be improved by carrying out the reaction using a stirrer with strong shear force such as a homomixer, homogenizer, clearmix, or ball mill to stir the reaction during the reaction, and mixed esterified polysaccharide nanofibers can be obtained with the fiber length cut to the required range.
[0073] When defibrating the mixed esterified polysaccharide after the mixed esterification, the mixed esterified polysaccharide can be synthesized, washed, neutralized, dispersed in a polar solvent such as water or an aqueous solution of 50% or less polar solvent, and defibrated by applying shear force to obtain mixed esterified modified polysaccharide nanofibers. Water (distilled water) is the most preferable dispersion solvent due to the electrostatic repulsion effect, but an aqueous solution of 50% or less polar solvent such as alcohol may be used for the convenience of concentrating the polysaccharide nanofibers after nanoization and defibration.
[0074] The mixed esterified polysaccharide nanofiber of the present invention preferably has a crystal structure of a natural polysaccharide.
[0075] The degree of crystallinity of the mixed esterified modified polysaccharide nanofiber of the present invention is 30% to 75%. If the degree of crystallinity is higher than 75%, the content of nanofibers having a fiber diameter of 20 nm or more is high, and the transparency of the aggregate is low, which is not preferable. On the other hand, if the degree of crystallinity is 30% or less, the content of amorphous polysaccharide increases, which is not preferable because there is a risk of the reinforcing effect and thickening effect being reduced. More preferably, the degree of crystallinity is 35 to 69%, and most preferably 40 to 68%.
[0076] The average fiber length of the mixed esterified polysaccharide nanofiber is 100 nm or more and less than 5000 nm. If it is shorter than this range, the reinforcing effect, thickening effect, and water retention effect are reduced, which is not preferable. On the other hand, if it is 5 μm or more, it is not preferable because it is easy to aggregate when compounded with a polymer and the reinforcing effect cannot be expressed. Furthermore, if the fiber length is too long, the viscosity increases significantly when added to a paint or adhesive, and there is a risk that the paint or adhesive will lose its fluidity and processability, which is not preferable. The average fiber length of the mixed esterified polysaccharide nanofibers is more preferably from 200 nm to 2000 nm, and most preferably from 300 to 1000 nm.
[0077] The visible light transmittance of a 0.3 wt% aqueous dispersion of the mixed esterified polysaccharide nanofiber of the present invention is 50% or more. If it is less than 50%, the transparency of the reinforced composite and dispersion is low, which is not preferable. If the visible light transmittance is 50% or more, the fiber diameter is small and the transparency of the reinforced composite and dispersion is high, which is preferable. The visible light transmittance is more preferably 60% or more, and most preferably 65%. EXAMPLES
[0078] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. Table 1 shows the composition of the reaction solution and the reaction conditions in the examples and comparative examples. The details of the raw materials used are as follows, and the properties of the obtained mixed esterified polysaccharides or mixed esterified polysaccharide nanofibers were measured as follows.
[0079] (Materials and solvents used) As the cellulose pulp, commercially available softwood pulp (manufactured by Georgia Pacific, product name: Fluff Pulp ARC48000GP) was used as is without drying. Chitin was purchased from Tokyo Kasei and used as is without pretreatment. Potato starch was purchased from Nacalai Tesque, Inc. and used as is. Other reagents were purchased from Nacalai Tesque, Inc. and used as is.
[0080] (Equipment used for reaction and defibration) The mixed esterification modification reaction of polysaccharides was carried out using a 20 ml sample bottle, a magnetic stirrer, or a magnetic hot stirrer. The mixed esterification polysaccharides were defibrated into nanofibers using a Panasonic MX-X701-T mixer.
[0081] (FT-IR analysis) The IR spectrum of the mixed esterified polysaccharide or the mixed esterified polysaccharide nanofiber was measured by a Fourier transform infrared spectrophotometer (FT-IR). The measurement was performed using a NICOLET MAGNA-IR760 Spectrometer manufactured by NICOLET, and analysis was performed in ATR mode.
[0082] (Evaluation of sulfate esterification modification rate of mixed esterified polysaccharides or polysaccharide nanofibers) The sulfate esterification modification rate of the mixed esterified polysaccharide or polysaccharide nanofiber was evaluated as follows. First, the sulfur content of the mixed esterified polysaccharide or polysaccharide nanofiber was quantified by the combustion absorption-IC method. That is, the dried mixed esterified polysaccharide or polysaccharide nanofiber (0.01 g) was placed on a magnetic board and burned in an oxygen atmosphere (flow rate: 1.5 L / min) in a circular furnace (1350 °C), and the generated gas components were absorbed in 3% hydrogen peroxide solution (20 ml). The obtained absorption liquid was made up to 100 ml with pure water, and the molar concentration of sulfate ions was calculated from the ion chromatography measurement results of the diluted liquid. The molar concentration of sulfate ions was converted to the number of millimoles of sulfate groups per 1 g of mixed esterified polysaccharide or polysaccharide nanofiber, and the sulfate esterification modification rate (mmol / g) was obtained. The combustion absorption-IC method was performed using ICS-1500 manufactured by Nippon Dionex Co., Ltd.
[0083] (Evaluation of the acylation modification rate of mixed esterified polysaccharides or polysaccharide nanofibers) The acylation modification rate was quantified as follows. That is, 0.1 g of mixed esterified polysaccharide or polysaccharide nanofiber was placed in a mixture of ethanol and sodium hydroxide aqueous solution, and hydrolysis was carried out at room temperature for 2 hours to cleave the ester bond between the acyl group and the hydroxyl group and convert the acyl group to a carboxylic acid. After hydrolysis, the solid content was removed, and the number of moles of carboxylic acid was quantified by the dropping method. The number of moles of carboxylic acid was converted to the number of millimoles of acyl groups per 1 g of mixed esterified polysaccharide or polysaccharide nanofiber, and this was taken as the acylation modification rate (mmol / g). Hydroxyl group modification rate (mmol / g) = sulfate ester modification rate + acylation modification rate
[0084] (Measurement of visible light transmittance) A 0.3% by weight aqueous dispersion of the mixed esterified modified cellulose nanofiber aggregate was prepared and measured using a UV-visible spectrophotometer to measure the visible light transmittance at a wavelength of 589 nm (D-ray). The device used for the measurement was Shimadzu UV-3600, and the measurement wavelength range was 300 nm to 800 nm.
[0085] (SEM observation) The shape of the mixed esterified polysaccharide nanofibers was observed using FE-SEM (JSM-6700F manufactured by JEOL Ltd., measurement conditions: 20 mA, 60 seconds).
[0086] (TEM observation) The TEM observation sample was observed in a TEM bright field at an acceleration voltage of 120 kV using a field emission transmission electron microscope (FE-TEM) JEM-2100F manufactured by JEOL Ltd.
[0087] (Pyrolysis GC-MS) The measurement conditions for the pyrolysis GC-MS of mixed esterified polysaccharides are as follows. Pyrolysis equipment: Frontier Labs "PY-2020D" Pyrolysis conditions: furnace temperature 200°C, heating time 1 minute, interface temperature 250°C GC-MS analyzer: Agilent's "GC6890" / JEOL's "JMS-Q1050GC" Separation column: Agilent "DB-5ms" Carrier gas: Helium Inlet temperature: 250℃ Column temperature: 40℃ (1 minute hold) - 10℃ / min increase - 250℃ Split mode: 50:1 MS scan range: 10~500amu
[0088] [Example 1] According to the weights shown in Table 1, 98% concentrated sulfuric acid, formamide, and acetic anhydride as a carboxylic acid anhydride were each placed in a 20 ml sample bottle, and stirred at room temperature for 1 minute using a magnetic stirrer to prepare a mixed esterification reaction solution. Next, 0.3 g of cellulose pulp was added, transferred to a magnetic hot stirrer set at 70 °C, and stirred for a specified time. The temperature of the mixture in the sample bottle was 50 °C. After stirring for 3 hours, the reaction liquid was placed in 150 ml of distilled water and stirred for 3 minutes, and then the solids were collected by filtration. The collected solids were again added to 150 ml of distilled water, stirred for 3 minutes, and filtered. After removing the reaction liquid such as acetic anhydride, sulfuric acid, and formamide by repeated stirring and filtration three times, the sulfate group was neutralized using a 0.1 wt% aqueous solution of sodium carbonate. Next, the sample was dried in a blower dryer at 105 °C for 2 hours, and then analyzed by FT-IR. The obtained IR spectrum is shown in Figure 1. Frequency 1250cm -1 and 1730cm -1 Absorption bands due to S=O and C=O were detected near the nucleus. The quantitative results of each modification rate are shown in Table 2.
[0089] [Example 2] Except for using chitin instead of cellulose, a mixed esterification reaction was carried out using the same procedure and technique as in Example 1 under the conditions shown in Table 1. The obtained mixed esterified chitin was washed and analyzed in the same manner as in Example 1. The IR spectrum (FIG. 2) showed that the chitin was ionized at a frequency of 1205 to 1250 cm -1 and 1730cm -1 Absorption bands due to S=O and C=O were detected in the 1H-CNT. The quantitative results of each modification rate are shown in Table 2.
[0090] [Example 3] A mixed esterification reaction was carried out in the same manner as in Example 1, except that potato starch was used instead of cellulose, and a mixed solution of ethanol and distilled water (50 / 50, weight ratio) was used instead of the distilled water used in washing under the conditions shown in Table 1. The mixed esterified starch obtained was washed with a mixed solution of distilled water and ethanol. After drying, it was subjected to FT-IR analysis. From the IR spectrum (FIG. 3), it was found that the frequency of 1205 to 1250 cm-1 and 1730cm -1 Absorption bands due to S=O and C=O were detected in the 1H-CNT. The quantitative results of each modification rate are shown in Table 2.
[0091] [Example 4] Mixed esterified cellulose was prepared under the same conditions as in Example 1, and after neutralization and washing, distilled water was added without drying to prepare 100 ml of a dispersion. The dispersion was placed in a mixer and stirred for 3 minutes to obtain a dispersion of mixed esterified cellulose nanofibers (the appearance photograph is shown in Figure 4). The visible light transmittance of the dispersion was measured and found to be 89%. The evaluation results of the modification rate are shown in Table 2. Meanwhile, an SEM photograph of the obtained mixed esterified modified cellulose nanofibers is shown in Figure 5. Nanofibers with a width of 10 nm or more were hardly observed, and the length was several hundred nm.
[0092] [Example 5] Mixed esterified modified cellulose nanofibers were prepared in the same manner as in Example 4, except that the reaction temperature was room temperature. A photograph of the appearance of the resulting dispersion of mixed esterified modified cellulose nanofibers is shown in Figure 4, and other evaluation results are shown in Table 2. The fiber length of the resulting mixed esterified CNF was several hundreds of nm, and almost no CNF with a width of 10 nm or less was observed.
[0093] [Examples 6 to 10] Mixed ester modified cellulose nanofibers were prepared according to the same procedure as in Example 4 using the compositions and reaction conditions shown in Table 1. Appearance photographs of each dispersion are shown in Figure 4, and other evaluation results are shown in Table 2. Furthermore, SEM and TEM photographs of the mixed ester modified cellulose nanofibers obtained in Example 7 are shown in Figure 6, and the results of pyrolysis GC-MS analysis are shown in Figure 7. Butyric acid was detected from the heating GC-MS analysis. The butyryl groups of the mixed esterified cellulose nanofibers were decomposed and converted to butyric acid. Meanwhile, SEM and TEM photographs of the mixed esterified cellulose nanofibers obtained in Example 9 are shown in Figure 8. The width of the CNFs was 10 nm or less, and the length was several hundreds of nm.
[0094] [Examples 11 and 12] Mixed esterified chitin was prepared under the same conditions as in Example 2, and then distilled water was added without drying to prepare 100 ml of a dispersion. The dispersion was placed in a mixer and stirred for 3 minutes to obtain a dispersion of mixed esterified chitin nanofibers (appearance photograph shown in Figure 4). SEM and TEM photographs of each are shown in Figures 9 and 10. Other evaluation results are shown in Table 2. The width of the obtained mixed esterified chitin nanofibers was slightly larger than that of the mixed esterified CNFs of Examples 4 to 10, being 10 nm or more, and the length was several hundred nm.
[0095] [Comparative Examples 1 to 3] Cellulose was reacted according to the same procedure as in Example 1 using the compositions and conditions shown in Table 1, but modification and micronization were not achieved in any case, and the cellulose remained unmodified.
[0096] Table 1. Reaction conditions for Examples and Comparative Examples [Table 1]
[0097] Table 2. Evaluation results of Examples and Comparative Examples [Table 2] [Industrial Applicability]
[0098] The mixed esterified polysaccharides or mixed esterified polysaccharide nanofibers of the present invention can be used as reinforcing materials, dispersants, or water-retaining / moisturizing agents in various composite materials, coating agents, cosmetics, etc., and can also be formed into sheets or films for use.
Claims
1. A mixed esterified polysaccharide, characterized in that the hydroxyl groups of the polysaccharide are modified with sulfate ester groups and acyl groups.
2. 2. The mixed esterified polysaccharide according to claim 1, wherein the modification rate of the hydroxyl groups is 0.3 to 19 mmol / g, and the molar ratio of sulfate ester groups to acyl groups is 10 / 90 to 99 / 1.
3. The mixed esterified polysaccharide according to claim 1, characterized in that the modification rate of the hydroxyl groups is 0.3 to 12.0 mmol / g, the molar ratio of sulfate ester groups to acyl groups is 10 / 90 to 99 / 1, and the mixed esterified polysaccharide is a nanofiber having an average fiber diameter of 1 nm to 500 nm.
4. The mixed esterified polysaccharide according to any one of claims 1 to 3 is dispersible or soluble in water or one or more organic solvents selected from the group consisting of DMSO, DMAc, DMF, amide solvents, alcohols, and ether solvents.
5. A method for producing a mixed esterified polysaccharide, comprising: permeating and swelling a polysaccharide with a mixed esterification reaction solution containing a protic amide solvent, a monobasic carboxylic acid anhydride, and sulfuric acid, as shown in the following formula (1), and subjecting the polysaccharide to an acylation reaction together with sulfate esterification: R1-C(=O)-NH(R2) (1) (In the formula, R1 and R2 represent a proton or an alkyl group having 1 to 3 carbon atoms. R1 and R2 may be the same or different.)
6. 6. The method for producing mixed esterified polysaccharides according to claim 5, wherein the protic amide solvent is at least one of formamide, N-methylformamide, acetamide and N-methylacetamide.
7. The method for producing a mixed esterified polysaccharide according to claim 5 or 6, characterized in that the concentration of the monobasic carboxylic acid anhydride in the mixed esterification reaction solution is 0.1 to 50% by weight, and the concentration of sulfuric acid is 0.1 to 50% by weight.
8. The method for producing a mixed esterified polysaccharide according to claim 5 or 6, characterized in that the concentration of the monobasic carboxylic acid anhydride in the mixed esterification reaction solution is 0.1 to 25% by weight, the concentration of the sulfuric acid is 0.1 to 20% by weight, and the mixed esterified polysaccharide is a nanofiber having an average fiber diameter of 1 nm to 500 nm.
Citation Information
Patent Citations
Dicarboxylic acid monoesterification modified cellulose nanofiber
JP2022030446A
Modified cellulose fine fibers and method for producing same
WO2017073700A1
Method for producing cellulose fine fiber
WO2017208600A1
Sulfuric acid esterification modified cellulose nanofibers and method for producing cellulose nanofibers
WO2018131721A1
